(untitled) - Thompson, Lawrence M. (Research Triangle Park, NC, 2008)
The new edition of a text introducing the principles of data communication such that the reader can move on to more specialized literature and technical conversations. Chapters cover serial communications standards, local area networks, network software, industrial networks and fieldbuses, wide area networks, and internetworking. The author assumes some general technical education and a basic computer literacy.
Mạng công nghiệp và truyền thông
Keywords: Hệ thống truyền dữ liệu,Data transmission systems